Brood stock formation of the hermaphrodite finfish species Pagellus erythrinus (common Pandora) from fish reared in captivity - KLAOUDATOS, S.D.; KLAOUDATOS, D.S. (Mediterranean Marine Science, 2004)
Formation of brood stock is considered to be one of the most important operations in order to acquire eggs and fry from any promising candidate finfish species for aquaculture production. The sex reversal observed in hermaphrodite species adds to confusion and creates additional complications in forming a brood stock. The present study describes the efforts and the results of the brood stock formation of the hermaphrodite finfish species Pagellus erythrinus (common Pandora) from individuals aged between 4 and 5 years (TL>300mm) reared in floating cages. Six groups were formed (50 fish/group) in all of which females were present comprising 20 to 40% of the population. The presence of females was in contrast to the literature, which reported that sex reversal of the common Pandora is complete in naturally occurring populations with the absence of females in sizes of a total length greater than 220mm, indicating that in captivity sex reversal is not complete for this species. Four of the groups formed spawned under natural environmental conditions without hormonal treatment and the other two groups were administered a different dosage (250 and 500 IU/kg) of Human Chorionic Gonadotropin (HCG) to induce spawning. The reproductive period started in the middle of May and ended at the beginning of July and spontaneous spawning occurred in all groups. Egg release lasted for a mean period of one month for the groups that spawned without hormonal treatment with no significant difference in the number of viable eggs between groups. The groups that spawned under hormonal treatment released eggs for a period of six and seven days, for the group that spawned under the high and low hormonal treatment, respectively, with no significant difference in the number of viable eggs between them. The hormonal induced spawning resulted in egg release within a short period of time ideal for a hatchery. However, the number of viable eggs produced was significantly lower compared to the number of viable eggs produced from groups that spawned without hormonal treatment.